Scenario of the commercialization of fairkeepers in the municipality of Bom Jardim in the State of Maranhão: before and during the pandemic (Research, Society and Development, 2021)
In the midst of a pandemic outbreak, all sectors of the economy were affected, to a greater or lesser extent, from raw materials, processing, to services, with restrictive circulation measures impacting production systems and marketing networks, due to this event, both producers and marketers had to adapt to other changes as to the way in which their products were marketed. Due to the great importance of the subject in question, the main objective of this work was to analyze and evaluate the situation of the market vendors, regarding the commercialization of their products, taking into account the social and economic aspects to obtain relevant information about the real commercial situation. at the main fair in the municipality of Bom Jardim before and during the pandemic. Through the collection of materials through a questionnaire. In this context, it was possible to present a brief overview of the situation among family farmers, most of the marketers who reported not having difficulties with the changes imposed by the pandemic were those who managed to adapt to the opportunities brought by the crisis, they had the need to to remain active even in the face of adversity, and continued to develop resilience agriculture. We obtained in the results, expressive percentages show how much the covid-19 pandemic impacted in the way of life in relation to the commercialization of the marketers. Through the analysis of the data collected, recommend more investments in the market infrastructure to accommodate marketers providing organization and hygiene.